Historical trend of Visceral Leishmaniasis in Brazil: epidemiological aspects and perspectives for the future (Research, Society and Development, 2023)
Visceral leishmaniasis (VL) still persists as an important public health problem in Brazil and has shown signs of increasing cases in recent years. Therefore, in the present work, a classic epidemiological research of quantitative, descriptive and exploratory character, the objective of this study was to evaluate the spatiotemporal distribution of this protozoal disease in the country and its different socio-administrative regions, while observing its distribution profile by age and gender, using secondary databases available on government websites. It was observed that the northern and northeastern regions, particularly the northern region, were the most affected, possibly due to environmental factors such as climatic conditions, density of forested areas, and diversity of sand fly species that prevail in this region. It was also possible to observe a significantly higher number of cases among men and children, possibly related to the activity patterns that men engage in and physiological and immunological factors related to children. The results obtained allow us to emphasize the design of prevention strategies aimed at minimizing the morbidity resulting from VL, such as treatment and population control of dogs, as well as the implementation of educational measures and strategic vector control.